(3GdEjVGMs - (3GdCROj, GdfjSGHhQj, CHh eMeO, GdaVd Hf TGPGf Hf GdNdjd, J (B260 (3g`s ((3GdfLas)
(3ChdgG (B:s
(3GdMeO ddg GdPj Ndb GdSehGJ hGdCQV(B... (3CeG HYO, aEfG fXQfG ajeG GNJda ajg Cgd GdedI ef Cgd GdbHdI ef CeQ Ojfge MJi caQ HYVge HYVG(B...s
(3BNQgG (B:s
(3agPg UaJce GdJj JYQahfgG ef CfaSce hJfWb HgG Ydjce CdSfJce(B. (3aGdMeO ddg GdPj HUQfG eG LgdJe(B...s
(3JHUQI GdYfhGf (B:s
(3EjVGM OaGFf GdfhGUHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B5(3, U(B149s
(3GdPQjYI, Qbe(B: 1926s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds